Waiting times for outpatient visits during military conflict: An observational study - Jacob Dreiher; Sharon Einav; Shlomi Codish; Amit Frenkel (PLoS ONE, 2025)
Background Environmental events, including military conflicts, may dramatically affect a hospital’s ability to provide routine treatments while maintaining reasonable waiting times. Objective To examine the impact of a military conflict (“Protective Edge”, PE) on the volume of activity and waiting times for outpatient clinics in a tertiary medical center. Methods Outpatient visits during PE (July-August 2014) were compared to outpatient visits during July-August 2013 (pre-conflict period) and 2015 (post-conflict period) with regards to the daily number of visits and waiting times. Clinics with at least 5,000 annual visits were included. Quantile regression adjusted for confounders was used for the multivariable models, in a stratified analysis by specialty. Results There were 87,495 outpatient visits during PE and 197,029 visits during the pre- and post-conflict periods. An 11% decrease in the daily number of visits was noted (ranging from 6% decrease in oncology and cardiology to 19–20% decrease in psychiatry and pediatrics). During PE, statistically significant longer waiting times were found for surgery (+1.0 day) and imaging (+1.1 days), while a 2.4 days decrease was noted in pediatrics, controlled for age, sex, ethnicity and the daily number of visits. Median waiting times were unchanged for cardiology, medicine, psychiatry and cardiology. Conclusions In the midst of a continuing military conflict, there was a notable increase in outpatient visit waiting times in some disciplines, but not all, despite a reduction in the overall volume of visits. Investigating whether similar impacts on patient care occur during other military conflicts or pandemics necessitates further research.